Monitoring and Control Over Managerial Decision-Making in Government Authorities - Zoska, Yana Volodymyrivna; Martyshyn, Denys Serhiyovych; Zaiats, Nataliya V`yacheslavivna; Arabadzhyiev, Dmytro Yuriyovych; Kapitanets, Svitlana Volodymyrivna (Globeedu Group, 2020)
The present academic paper considers the current problem of improving the efficiency of managerial decision-making in government authorities through the use of rational tools for monitoring and control. The welfare of society and the level the country’s development depend on these decisions, and control is an effective means of influencing the system of public administration. The purpose of the study is to systematize and harmonize the methodological provisions of monitoring and control of public administration, which are implemented through the process of managerial decision-making. Dialectical and logical methods, methods of analysis and synthesis, comparison and classification, as well as the matrix method have been used in the academic paper.

У статті розглядається актуальна проблема підвищення ефективності прийняття управлінських рішень органів влади за рахунок застосування раціональних інструментів моніторингу і контролю. Від цих рішень залежить добробут суспільства і рівень розвитку країни, а контроль є дієвим засобом впливу на систему державного управління. Метою дослідження є систематизація та узгодження методичних положень моніторингу і контролю діяльності органів державного управління, що реалізуються через процес прийняття управлінських рішень. В роботі використано діалектичні та логічні методи, методи аналізу та синтезу, порівняння та класифікації, а також матричний метод.
Keywords: control, monitoring, managerial decisions, government authorities, public governance, public control, tools of control; контроль, моніторинг, управлінські рішення, органи влади, державне управління, громадський контроль, інструменти контролю